Modulation of PF10_0355 (MSPDBL2) Alters Plasmodium falciparum Response to Antimalarial Drugs - Van Tyne, Daria (American Society for Microbiology, 2013)
Malaria's ability to rapidly adapt to new drugs has allowed it to remain one of the most devastating infectious diseases of humans. Understanding and tracking the genetic basis of these adaptations are critical to the success of treatment and intervention strategies. The novel antimalarial resistance locus PF10_0355 (Pfmspdbl2) was previously associated with the parasite response to halofantrine, and functional validation confirmed that overexpression of this gene lowered parasite sensitivity to both halofantrine and the structurally related antimalarials mefloquine and lumefantrine, predominantly through copy number variation. Here we further characterize the role of Pfmspdbl2 in mediating the antimalarial drug response of Plasmodium falciparum. Knockout of Pfmspdbl2 increased parasite sensitivity to halofantrine, mefloquine, and lumefantrine but not to unrelated antimalarials, further suggesting that this gene mediates the parasite response to a specific class of antimalarial drugs. A single nucleotide polymorphism encoding a C591S mutation within Pfmspdbl2 had the strongest association with halofantrine sensitivity and showed a high derived allele frequency among Senegalese parasites. Transgenic parasites expressing the ancestral Pfmspdbl2 allele were more sensitive to halofantrine and structurally related antimalarials than were parasites expressing the derived allele, revealing an allele-specific effect on drug sensitivity in the absence of copy number effects. Finally, growth competition experiments showed that under drug pressure, parasites expressing the derived allele of Pfmspdbl2 outcompeted parasites expressing the ancestral allele within a few generations. Together, these experiments demonstrate that modulation of Pfmspdbl2 affects malaria parasite responses to antimalarial drugs.